PENDIDIKAN KARAKTER DALAM CERITA RAKYAT MANAMARMAKERI - Insum Malawat (Balai Bahasa Provinsi Papua, 2019)
Character education is the supplies to keep the integrity of nation as cultural nation. Character education have goal to develop Pancasila values, it is about student spirit developing until to be the great human and have nationalism and patriotism. As multicultural nation, Indonesian has social problems that was grown and developed there. The substance of character education is to build nation in multicultural living and to build the civil behavior that love to tolerance, creative, independent, and cooperative to other ethnics. A source of character education is folktale. In Papuan context, the folktale is needed as a source material of character education. Varian of oral literary in folktale shows Papuan identity as multicultural domain in this nation. Folktale can be a medium to introduce Papuan; their community, their culture, its ecology and social life. For Papuan’s build and its progress not only use its natural resource. Human resource is priority for to do it. The human resource is important to build characters of young Papuan. It has written on Pancasila.